Development of PjBL-Based STEM E-Modules on Colloidal Materials - Geby S. Sihombing; Eddiyanto Eddiyanto (Universitas Tadulako, 2025)
The Industrial Revolution 4.0 demands improvements in the quality of education to produce superior human resources. In learning chemistry, especially colloid materials, students still have difficulty understanding abstract concepts and show low science literacy. This study aims to determine the needs analysis, the feasibility of e-modules, and the improvement of student learning outcomes using STEM e-modules based on project-based learning on colloid materials. This study was conducted at SMAN 1 Percut Sei Tuan and the sample class Matlanfor. The research method used is Research and Development (R & D), and the development model is ADDIE. Data collection is through interviews, observations, questionnaires, and tests. Data analysis of learning outcomes improvement uses the N-Gain test. The results obtained indicate that teachers have not maximised the use of the PjBL learning model and have never used PjBL-based STEM E-Modules; the books used do not contain projects or STEM. 77% of students reported feeling bored during the learning process because the media used or the teacher's teaching methods were less engaging. 92% need new teaching materials to improve students' knowledge of colloid learning through PjBL-based STEM E-Modules. The project-based learning (STEM) e-module on colloidal materials had a feasibility of 90.39%, categorised as very high, and was declared feasible. The learning outcomes of students who were treated with the PjBL-based STEM e-module increased by 72.47%.